Oxygen-doped carbon nanotubes for near-infrared fluorescent labels and imaging probes - Iizumi, Yoko (Sci Rep, 2018)
Chemical modification of carbon nanotube surface can controllably modulate their optical properties. Here we report a simple and effective synthesis method of oxygen-doped single-walled carbon nanotubes (o-SWCNTs), in which a thin film of SWCNTs is just irradiated under the UV light for a few minutes in air. By using this method, the epoxide-type oxygen-adducts (ep-SWCNTs) were produced in addition to the ether-type oxygen-adducts (eth-SWCNTs). The Treated (6, 5) ep-SWCNTs show a red-shifted luminescence at ~1280 nm, which corresponds to the most transparent regions for bio-materials. Immunoassay, fluorescence vascular angiography and observation of the intestinal contractile activity of mice were demonstrated by using the produced o-SWCNTs as infrared fluorescent labels and imaging agents.